A review of encapsulation using emulsion crosslinking method - Jayanudin, Jayanudin; Heriyanto, Heri (World Chemical Engineering Journal, 2021)
Encapsulation is a process to protect active components or other materials in the form of liquids, solids, and gases which are sensitive to the environment using coating materials. Encapsulation can be used for the pharmaceutical, food, beverage, textile, and other industries. The encapsulation method has been developed depending on the active ingredient being protected and its function. The encapsulation method is generally divided into chemical and mechanical methods. This review aims to explain the emulsion crosslinking which is one of the encapsulation methods. This method was easy and simple, just add a crosslink agent to the emulsion and then the microparticles formed were washed, filtered, and dried. This review also reports several encapsulation studies using the emulsion crosslinking method.